Morphological Features of Vertebrates’ Lung Adaptation to Environment - Saparov, Kuandyk; Olzhabayeva, Zhanna; Zharkova, Irina; Mankibaeva, Sandugash; Jumasheva, Rakhima; Tursynbay, Akerke; Aubakirova, Aiman (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses morphological changes in the lung structure during environmental adaptation. Adaptive reactions of amphibians, reptiles, and some mammals living in the steppe and mountain regions were studied at the ultrastructural level. The obtained materials revealed the features of the pulmonary epithelium of vertebrate animals living in different biotopes. The airborne barrier of representatives of the species of reptiles, amphibians, and mammals had a different structure depending on the habitat of the terrestrial vertebrate. An increased, intense, and also very small secretion of surfactant was observed - a mixture of surfactants lining the pulmonary alveoli. Aeromatological membranes had different thicknesses in the studied animals. In populations of the mountainous region of vertebrates, a thinning of the airborne membrane system, an increase in the airway area, and a decrease in the number of mucous cells were observed. In vertebrate populations living in the steppe zones, increased secretion of surfactant, mucosal hyperplasia, and fluid loss in the superficial airways was revealed. The thickness of the airborne membrane system was significant. Increased secretion of mucosal cells and increased secretion of "mixed" type cells were detected using a scanning microscope.